2004
DOI: 10.1128/mcb.24.21.9295-9304.2004
|View full text |Cite
|
Sign up to set email alerts
|

Conditional Activation of Akt in Adult Skeletal Muscle Induces Rapid Hypertrophy

Abstract: Skeletal muscle atrophy is a severe morbidity caused by a variety of conditions, including cachexia, cancer, AIDS, prolonged bedrest, and diabetes. One strategy in the treatment of atrophy is to induce the pathways normally leading to skeletal muscle hypertrophy. The pathways that are sufficient to induce hypertrophy in skeletal muscle have been the subject of some controversy. We describe here the use of a novel method to produce a transgenic mouse in which a constitutively active form of Akt can be inducibly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
291
2
8

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 384 publications
(314 citation statements)
references
References 27 publications
13
291
2
8
Order By: Relevance
“…Alternatively, myostatin has been observed to promote adipogenesis in multipotential mesenchymal cells, suggesting that loss of myostatin function may directly suppress adipocyte differentiation. 9 Our results are consistent with these in vitro findings; however, it is also known that other mouse models showing increased muscle mass, such as transgenic mice overexpressing IGF-1, 10,11 Akt, 12 and ski 13 show decreased fat mass. It is therefore possible that an indirect effect of double-muscling on fat metabolism may also be involved in the resistance to body fat accumulation in the myostatin-deficient animals; however, indirect calorimetry studies have found no significant differences in the respiratory exchange ratio between normal mice and myostatin-deficient rodents.…”
Section: Discussionsupporting
confidence: 91%
“…Alternatively, myostatin has been observed to promote adipogenesis in multipotential mesenchymal cells, suggesting that loss of myostatin function may directly suppress adipocyte differentiation. 9 Our results are consistent with these in vitro findings; however, it is also known that other mouse models showing increased muscle mass, such as transgenic mice overexpressing IGF-1, 10,11 Akt, 12 and ski 13 show decreased fat mass. It is therefore possible that an indirect effect of double-muscling on fat metabolism may also be involved in the resistance to body fat accumulation in the myostatin-deficient animals; however, indirect calorimetry studies have found no significant differences in the respiratory exchange ratio between normal mice and myostatin-deficient rodents.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, in addition to acting as an inductive cue for hypertrophy, activation of the Akt/mTOR pathway could also prevent muscle atrophy in vivo. 30,32,33,43 Furthermore, it has been shown in vitro that the overexpression of Src homology 2 domain-containing inositol-5Ј-phosphatase 2, which like PTEN decreases PiP 3 level, led to atrophy, whereas the overexpression of a dominant negative mutant, which increases PiP 3 level, induced hypertrophy. 32 The overexpression of inositol-5Ј-phosphatase 2 in healthy mice muscle had no effect on fiber size but the overexpression of the phosphatase in a model of compensatory hypertrophy completely blocked the hypertrophy response.…”
Section: Discussionmentioning
confidence: 99%
“…Active Akt has been found significantly reduced in different models of skeletal muscle atrophy, such as unloading and denervation (50), whereas transgenic mice overexpressing Akt are protected against denervation-induced muscle atrophy (7). Hyperexpression of Akt in skeletal muscle cells or its conditional activation in the skeletal muscle of adult rats results in a hypertrophic phenotype (39,47). Not only does activation of Akt stimulate protein synthesis through regulation of glycogen synthase kinase-3␤ and mTOR (mammalian target of rapamycin) kinases (7), but it also may downregulate protein breakdown.…”
Section: Discussionmentioning
confidence: 99%